Psychometric Evaluation of a Cross-Culturally Adapted Felt Stigma Questionnaire Among People Living with HIV in Kenya. - Kingori, Caroline; Reece, Michael; Obeng, Samuel; Murray, Maresa; Shacham, Enbal; Dodge, Brian; Akach, Emannuel; Ngatia, Peter; Ojakaa, David (ResearchGate, 2013)
Psychometric properties of an 18-item HIV felt stigma questionnaire were evaluated utilizing data collected froma diverse ethnic and socioeconomic group of 370 people living with HIV/AIDS and receiving HIV/AIDS-relatedhealth services at an HIV clinic in Kenya. Factor analyses revealed a four factor solution (public attitudes,ostracize, discrimination, personal life disrupted) based on the Scree plot with explained variance of 44% thathad Eigen values greater than 1.00. The retained felt stigma items revealed a Cronbach’s alpha coefﬁcient of0.828, while the four factors had coefﬁcient alphas ranging from 0.675 to 0.799. The adapted retained ques-tionnaire was deemed a practical guide for measuring felt stigma in a Kenyan cultural context to necessitateprovision of the most effective HIV-related mental health services to individuals living with HIV in Kenya
Keywords: Psychometric; Stigma; HIV/AIDS; Mental health; Kenya; PLWHA